Inhibition of COX-2/PGE2 cascade ameliorates cisplatin-induced mesangial cell apoptosis - Yu, Xiaowen (Am J Transl Res, 2017)
Cisplatin is one of the most potent cytotoxic drug for the treatment of many types of cancer. However, the side effects on normal tissues, particularly on the kidney, greatly limited its use in clinic. Emerging evidence demonstrated that cisplatin could directly cause mesangial cell apoptosis, while the potential mechanism is still elusive. Here we examined the contribution of COX-2 in cisplatin-induced mesangial cell apoptosis. Firstly, we found cisplatin induced cell apoptosis in mesangial cells shown by increased number of apoptotic cells in parallel with the upregulation of Bax and the downregulation of Bcl-2. Interestingly, cisplatin-induced cell apoptosis was accompanied by an upregulation of COX-2 at both mRNA and protein levels in dose- and time-dependent manners. Importantly, inhibition of COX-2 via a specific COX-2 inhibitor celecoxib markedly blocked cisplatin-induced mesangial cell apoptosis as evidenced by the decreased number of apoptotic cells, blocked increments of cleaved caspase-3 and Bax, and reversed Bcl-2 downregulation. Meanwhile, cisplatin-induced PGE2 production was markedly blocked by the treatment of celecoxib. In conclusion, this study indicated that COX-2/PGE2 cascade activation mediated cisplatin-induced mesangial cell apoptosis. The findings not only offered new insights into the understanding of cisplatin nephrotoxicity but also provided the therapeutic potential by targeting COX-2/PGE2 cascade in treating cisplatin-induced kidney injury.